Trabeculated (non-compacted) and compact myocardium in adults: the multi-ethnic study of atherosclerosis - Kawel, Nadine; Nacif, Marcelo; Arai, Andrew E; Gomes, Antoinette S; Hundley, William; Johnson, Craig; Prince, Martin R; Stacey, Brandon; Lima, Joao A; Bluemke, David A (Journal of cardiovascular magnetic resonance, 2012)
From: 15th Annual SCMR Scientific Sessions Orlando, FL, USA 2-5 February 2012 Author details1-Radiology and Imaging Sciences, National Institutes of Health, Bethesda, MD, USAEMPTY2-National Institute of Biomedical Imaging and Bioengineering, National Institutes of Health, Bethesda, MD, USAEMPTY3-National Heart, Lung and Blood Institute, National Institutes of Health, Bethesda, MD, USAEMPTY4-Department of Radiology, UCLA School for Medicine, Los Angeles, CA, USAEMPTY5-Department of Internal Medicine / Cardiology, Wake Forest University, Winston-Salem, NC, USAEMPTY6-Collaborative Health Studies Coordinating Center, University of Washington, Seattle, WA, USAEMPTY7-Cornell and Columbia Universities, New York, NY, USAEMPTY8-Division of Cardiology, Johns Hopkins University, Baltimore, MD, USAEMPTY Supplemental Information: Percent subjects with a T/M ratio >2.3 per region at the mid-cavity level (outer circle) and the apical level (inner circle) of the entire cohort (A) and the subset of subjects free of cardiac disease (B). [figure omitted; refer to PDF] Figure 2 Percent of subjects of the entire cohort (grey bars) and the subset of subjects free of cardiac disease (black bars) with a T/M ratio >2.3 in 0 to 8 regions per subject.